Picking pearls from the Silk Road: Insights into the spider (Arachnida, Araneae) diversity in Georgia from the Caucasus Barcode of life project. Part II - Armen Seropian; Natalia Bulbulashvili; Stefan Otto; Hans-Joachim Krammer; Nino Kachlishvili; Anastasia Datunashvili (Caucasiana, 2023)
Abstract Spiders collected during field trips and by spontaneous hand collection throughout Georgia between the years 2006 and 2023 were determined to species and partially assisted by genetic barcoding of the COI gene. Among the resulting 297 species, 100 species, 25 genera, and 1 family were recorded from Georgia for the first time, of which 18 species and 5 genera were recorded for the first time from the entire Caucasus. Of the 283 barcoded specimens representing 150 species, 26 were barcoded for the first time. 140 diagnostic drawings of 76 preserved specimens, along with photos of 15 preserved (Supplementary File) and one alive species, are provided. Baryphyma proclive (Simon, 1884), Pritha pallida (Kulczyński, 1897), and Zelotes khostensis Kovblyuk & Ponomarev, 2008 are indicated as the species with an Italo-Caucasian disjunctive distribution.